Administration of paracetamol versus dipyrone by intravenous patient-controlled analgesia for postoperative pain relief in children after tonsillectomy - Sener,Mesut (2015)
BACKGROUND AND OBJECTIVE: We compared the efficacy of intravenous (IV) paracetamol versus dipyrone via patient-controlled analgesia (PCA) for postoperative pain relief in children. METHODS: The study was composed of 120 children who had undergone elective tonsillectomy after receiving general anesthesia. Patients were divided into 3 groups according to the dosage of postoperative intravenous-patient-controlled analgesia: paracetamol, dipyrone, or placebo. Pain was evaluated using a 0- to 100-mm visual analog scale and 1- to 4-pain relief score at 30 min, 1, 2, 4, 6, 12, and 24 h postoperatively. Pethidine (0.25 mg kg-1) was administered intravenously to patients requiring rescue analgesia. Pethidine requirements were recorded during the first 24 h postoperatively, and treatment related adverse effects were noted. RESULTS: Postoperative visual analog scale scores were significantly lower with paracetamol group compared with placebo group at 6 h (p < 0.05), dipyrone group compared with placebo group at 30 min and 6 h (p < 0.05). No significant differences regarding visual analog scale values at 1, 2, 4, 12, and 24 h were found. No significant differences were found between groups with respect to pain relief score (p > 0.05). Postoperative pethidine requirements were significantly lower with paracetamol and dipyrone groups compared with placebo group (62.5%, 68.4% vs 90%, p < 0.05). No significant differences were found between groups with respect to nausea, vomiting and the any other adverse effects of the drugs (p > 0.05). CONCLUSIONS: Paracetamol and dipyrone have well tolerability profile and effective analgesic properties when administered IV-PCA for postoperative analgesia in children after tonsillectomy.